2011
DOI: 10.1080/10438591003669743
|View full text |Cite
|
Sign up to set email alerts
|

R&D cooperation versus R&D subcontracting: empirical evidence from French survey data

Abstract: This paper uses a survey of French firms active in R&D to identify the determinants of the trade-off between R&D subcontracting and R&D cooperation. We observe that R&D subcontracting is more likely than R&D cooperation when the partner is chosen on objective criteria, such as prices, quality certificates and geographic proximity. Subcontracting relationships also involve less uncertainty, are less likely to lead to patent deposits and less frequently involve public research institutions. These results are coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…The results also temper the fear of Grimpe and Kaiser (2010) that too much R&D outsourcing erodes firm heterogeneity, since the focal firm keeps investing in internal capabilities. Our results further strengthen the study by Dhont-Peltrault and Pfister (2011), who found a modest positive impact of R&D intensity on R&D outsourcing intensity, while measuring this by the number of partnership interactions rather than by the actual outsourced R&D expenditures over turnover or employment. The presence of employees with higher education, on the contrary, does not influence the R&D outsourcing intensity, but it does affect the probability to start R&D outsourcing activities as put forward by the relational view (Martinez-Noya et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The results also temper the fear of Grimpe and Kaiser (2010) that too much R&D outsourcing erodes firm heterogeneity, since the focal firm keeps investing in internal capabilities. Our results further strengthen the study by Dhont-Peltrault and Pfister (2011), who found a modest positive impact of R&D intensity on R&D outsourcing intensity, while measuring this by the number of partnership interactions rather than by the actual outsourced R&D expenditures over turnover or employment. The presence of employees with higher education, on the contrary, does not influence the R&D outsourcing intensity, but it does affect the probability to start R&D outsourcing activities as put forward by the relational view (Martinez-Noya et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…In other words, following Dhont -Peltrault and Pfister (2011), the foreign subsidiaries of our sample are relatively more willing than domestic groups to develop a technology or product with local partners. By contrast, they seem less willing than domestic firms to delegate these tasks to local partners.…”
mentioning
confidence: 99%
“…For example, it included research that explored the determining factors in terms of intellectual property issues (e.g. Ulset, 1996;Dhont-Peltrault and Pfister, 2006;Gooroochurn and Hanley, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%